Exosome engineering in cell therapy and drug delivery - Sadeghi, Somaye; Tehrani, Fahimeh Ramezani; Tahmasebi, Safa; Shafiee, Abbas; Hashemi, Seyed Mahmoud (Inflammopharmacology, 2023)
Cell-derived exosomes have opened new horizons in modern therapy for advanced drug delivery and therapeutic applications, due to their key features such as low immunogenicity, high physicochemical stability, capacity to penetrate into tissues, and the innate capacity to communicate with other cells over long distances. Exosome-based liquid biopsy has been potentially used for the diagnosis and prognosis of a range of disorders. Exosomes deliver therapeutic agents, including immunological modulators, therapeutic drugs, and antisense oligonucleotides to certain targets, and can be used as vaccines, though their clinical application is still far from reality. Producing exosomes on a large-scale is restricted to their low circulation lifetime, weak targeting capacity, and inappropriate controls, which need to be refined before being implemented in practice. Several bioengineering methods have been used for refining therapeutic applications of exosomes and promoting their effectiveness, on the one hand, and addressing the existing challenges, on the other. In the short run, new diagnostic platforms and emerging therapeutic strategies will further develop exosome engineering and therapeutic potential. This requires a thorough analysis of exosome engineering approaches along with their merits and drawbacks, as outlined in this paper. The present study is a comprehensive review of novel techniques for exosome development in terms of circulation time in the body, targeting capacity, and higher drug loading/delivery efficacies.